2001
DOI: 10.1596/0-8213-4958-9
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Alleviation in Jordan

Abstract: The findings, interpretations, and conclusions expressed in this book are entirely those of the authors and should not be attributed in any manner to the World Bank, to its affiliated organizations, or to members of its Board of Executive Directors or the countries they represent. The World Bank does not guarantee the accuracy of the data included in this publication and accepts no responsibility for any consequence of their use. The boundaries, colors, denominations, and other information shown on any map in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…In Jordan, Food consumption studies and surveys revealed that the per capita intake of the various food groups and their contribution of energy and nutrients have been changed since the mid of the last century (Alwan & Kharabsheh, 2006;FAO, 2003). Food subsidizing of some basic food commodities was canceled since 1997 (Shaban, Abu-Ghaida, & Al-Naimat, 2001). The absolute poverty line has risen to 814 Jordanian Dinars (JD) (equivalent to 1163 USD) per individual per year (DOS, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Jordan, Food consumption studies and surveys revealed that the per capita intake of the various food groups and their contribution of energy and nutrients have been changed since the mid of the last century (Alwan & Kharabsheh, 2006;FAO, 2003). Food subsidizing of some basic food commodities was canceled since 1997 (Shaban, Abu-Ghaida, & Al-Naimat, 2001). The absolute poverty line has risen to 814 Jordanian Dinars (JD) (equivalent to 1163 USD) per individual per year (DOS, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the full impact of SC decline is plagued by problems related to the quantity and quality of data. Several qualitative studies on poverty and social relations were carried out in Jordan since the early 1990s (e.g., see Abu-Odeh, 1999;CSS, 2003aCSS, , 2003bCunningham & Sarayrah, 1993;DFID, 2001;El-Said, 1996;Fathi, 1993;ICG, 2003aICG, , 2003bReiter, 2002;Shaban, Abu-Ghaida, and Al-Naimat, 2001;UNDP, 2004). Ironically, none of these studies cited earlier work on or used the term SC as a theoretical framework in their attempt to encapsulate the vitality of social and community relations, or as an analytic framework to study increased poverty, corruption, nepotism, and weak enforcement of the rule of law and regulations.…”
Section: (A) Measuring Social Capital In Jordanmentioning
confidence: 99%
“…This process will also help them to estimate accurately what they need (Friel et al, 2004). Generally, poor households are more careful in minimizing food wastage than their rich counterparts (for instance, see Shaban et al, 2001). Therefore, I assume a wastage level between 10% and 40% for LAC countries.…”
Section: Patterns Of Fandv Availability For Human Consumption In Lac Comentioning
confidence: 99%